Hybrid polystyrene based electrospun fibers with spin‐crossover properties. Issue 11 (21st March 2015) - Echeverria, Coro; Rubio, Miguel; Mitchell, Geoffrey R.; Roig, Anna; López, Daniel
ABSTRACT: We have succeeded in the preparation of electrospun fibers of polystyrene incorporating a metallo‐organic polymer of [Fe (II) (4‐octadecyl‐1, 2, 4‐triazole)3 (ClO4 )2 ] n . The obtained fibers have diameters in the range 2–4 µm and show the characteristic spin‐crossover transition associated with the metallo‐organic polymer. The structure of both, polystyrene and the metallo‐organic polymer, in the fibers was also studied. © 2015 Wiley Periodicals, Inc. J. Polym. Sci., Part B: Polym. Phys.2015, 53, 814–821 Abstract : Electrospun fibers of blends of [Fe(II)(4‐octadecyl‐1, 2, 4‐triazole)3 (ClO4 )2 ] n metallo‐organic polymer and atactic polystyrene that preserve the magnetic properties of the bulk metallo‐organic polymer and retain the properties of the atactic polystyrene are prepared. The obtained fibers have diameters of 2–4 µm and show the characteristic spin‐crossover transition associated with the metallo‐organic polymer. The structure of both polystyrene and the metallo‐organic polymer in the fibers is also studied.